Vital Signs Changes of Brick Industry Workers Exposed to Heat Pressure in Sukarami Palembang - Syokumawena Syokumawena; Marta Pastari; Rahmad A. Juliansyah; Hanna S.W. Kusuma; Dwi D. Rihibiha (Journal of Medicine and Health, 2018)
Brick workers are exposed to dust contained of mixtures of chemical substances andhigh temperature. Those environmental factors can affect the health status of the workers;mainly the cardiovascular system. The aim of this research was to observe the effect of heatpressure on vital sign of brick factory manufacturing workers in Sukarami Palembang. Theresearch was conducted in RT 07/13 Sungai Durian, Kecamatan Sukarami, Palembang. Thesubjects were 40 people brick workers; 20 workers were exposed to heat pressure and 20workers did not. We found that in the workers with heat pressure exposure,the average vitalsigns before working are blood pressure of 117/76 mmHg, pulse of 77 x/minutes, and bodytemperature of 36,5°C and after working are blood pressure of 130/84 mmHg, pulse of 92x/minutes, and body temperature of 38°C. In the workers without heat pressure exposure, theaverage vital signs before working are blood pressure of 107/80 mmHg, pulse of 75 x/minutes,and body temperature of 36°C and the average vital signs after working are blood pressure of112/81 mmHg, pulse of 79 x/minutes, and body temperature of 37°C. Conclusion, heat pressurehas effects on vital sign of brick factory manufacturing workers in Sukarami Palembang.Keywords: blood pressure, body temperature, brick factory pulse, heat pressure